Statement (draft)
028-0029-001 Issued by the Publicity Department of the Trades Union Congress. 28th October 1936 Having considered the proceedings of the Joint meeting of the Bureau of the L.S.I. and the Executive of the I.F.T.U. in Paris on October 26, 1936 this meeting declares that in conformity with the resolution passed by the Plymouth Trades Union Congress and the Conference of the Labour Party at Edinburgh it maintains the right of the constitutionally elected government of Spain in accordance with the practice of international law to secure the arms necessary to maintain the authority of constitutional government in Spain, and to re-establish law and order in her own territory. Having regard to the fact that the non-intervention agreement has proved ineffective in its operation this joint meeting considers that it is incumbent upon the French and British Governments to take the initiative for the conclusion of an international agreement which shall completely restore and implement complete commercial liberty to Republican Spain. 292/946/28/29